ASPP1 and ASPP2 are new transcriptional targets of E2F. - Fogal, V; Kartasheva, N; Trigiante, G; Llanos, S; Yap, D; Vousden, K; Lu, X (2005)
The E2F family of transcription factors regulates the expression of a number of genes whose products are involved in cell cycle control, DNA replication and apoptosis. We show here that E2F-1 binds in vivo the promoters of ASPP1 and ASPP2 genes, two activators of p53-mediated apoptosis, E2F-1, E2F-2 and E2F-3 all activate the isolated ASPP1 and ASPP2 promoters. Overexpression or deregulation of E2F-1 increased the expression levels of ASPP1 and ASPP2 mRNA and proteins. The identification of ASPP1 and ASPP2 genes as transcriptional targets of E2F provides another mechanism by which E2F cooperates with p53 to induce apoptosis.